2017
DOI: 10.1038/s41598-017-03381-w
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variability of trace elements fingerprints in cockle (Cerastoderma edule) shells and its relevance for tracing geographic origin

Abstract: Understanding spatio-temporal variability of trace elements fingerprints (TEF) in bivalve shells is paramount to determine the discrimination power of this analytical approach and secure traceability along supply chains. Spatio-temporal variability of TEF was assessed in cockle (Cerastoderma edule) shells using inductively coupled plasma-mass spectrometry (ICP-MS). Four elemental ratios (Mg/Ca, Mn/Ca, Sr/Ca and Ba/Ca) were measured from the shells of specimens originating from eight different ecosystems along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…We used the common cockle genetic map to ascertain the genetic component underlying the broad diversity observed for colour pattern on the wild populations of this species in the Northeast Atlantic. Ricardo et al (2017, 2022) showed an important variation in shell ion composition in common cockle, apparently related to environmental factors, that made possible to trace back the geographic origin of specimens, but they did not associate this variation with colour. Most phenotypes observed in wild populations in our study could be identified in the families produced at hatchery, although their intensity was somewhat faded, likely due to environmental factors operating across the lifespan of the adult specimens collected.…”
Section: Discussionmentioning
confidence: 94%
“…We used the common cockle genetic map to ascertain the genetic component underlying the broad diversity observed for colour pattern on the wild populations of this species in the Northeast Atlantic. Ricardo et al (2017, 2022) showed an important variation in shell ion composition in common cockle, apparently related to environmental factors, that made possible to trace back the geographic origin of specimens, but they did not associate this variation with colour. Most phenotypes observed in wild populations in our study could be identified in the families produced at hatchery, although their intensity was somewhat faded, likely due to environmental factors operating across the lifespan of the adult specimens collected.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, some studies have also focused on shell inorganic composition, because it provides a stable, long-term, site-specific marker of elements, which is strongly influenced by the environment. This specific fingerprint may be useful for geographical-origin traceability [ 17 , 18 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The shell chemical composition is strongly influenced by external variables, such as water temperature, salinity, pH, dissolved oxygen, sea currents, and coastal pollution, which can influence the growth rate, the calcium carbonate crystallization, and the possible inclusion of trace elements in the shell structure. The shell can be an excellent reservoir for the accumulation of foreign inorganic chemical species, allowing even long-term environmental changes to be recorded [ 2 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the spatio-temporal stability of geochemical tags is vital if such tags are to be informative. Some species, such as the cockle, Cerastoderma edule , demonstrate significant temporal variability in geochemical tags among years 51 , whereas other species show seasonal stability in geochemical tags e.g., the hardshell clam, Mercenaria mercenaria 52 . Analysing geochemical tags in mussels collected from Ahipara on a monthly timeframe (January, February, March, 2015) revealed that mussels could be assigned back to their site of origin (Ahipara) with a high degree of confidence (0.995–1.000), both in the context of the other five sites and also in terms of the month of collection (i.e., spatially and temporally).…”
Section: Discussionmentioning
confidence: 99%